1993
DOI: 10.1109/20.195745
|View full text |Cite
|
Sign up to set email alerts
|

Visible light emission measurements from a dense electrothermal launcher plasma

Abstract: A bstrocf-Measurements of the visible light obtaining quantitative data difficult. In this paper, we discuss emission from dense, weakly non-ideal Plasmas efforts to measure the average plasma temperature by using have been Performed On the the relative line ratio method. The results using this electrothermal launcher device "SIRENS". The technique are with the results o~conduc~vity, h a plasma is created by the ablation of a Lexan insulator in the source, which then flows through a flux, and mass loss methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Taylor 11,12 performed radiative heat flux measurements on plasmas emerging from a long capillary into stagnant air at 1 atm. The experimental configuration was similar to the one used by Hankins and Mann 13 and Hankins et al 14,15 A polyethylene capillary of about 175 mm in length was employed, coupled with very large input energy levels of 40 kJ. The copper initiation wire was 1 mm in diameter, which is significant.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor 11,12 performed radiative heat flux measurements on plasmas emerging from a long capillary into stagnant air at 1 atm. The experimental configuration was similar to the one used by Hankins and Mann 13 and Hankins et al 14,15 A polyethylene capillary of about 175 mm in length was employed, coupled with very large input energy levels of 40 kJ. The copper initiation wire was 1 mm in diameter, which is significant.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic plasma temperature is often measured at the torch exit channel via optical emission spectroscopy while thermal temperature distribution may be measured with specially coated thermocouples or via infrared thermometry [7,8]. The assumption of local thermodynamic equilibrium is usually valid for thermal plasma torches, similarly for electrothermal plasma sources [7,8,12,13]. Temperatures measured in argon gas plasma jets from a 100 kW DC plasma torch have been on the order of ~11,200 K [7], while the temperatures measured from a pulsed electrothermal plasma source range from 8,800 to 14,000 K [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The assumption of local thermodynamic equilibrium is usually valid for thermal plasma torches, similarly for electrothermal plasma sources [7,8,12,13]. Temperatures measured in argon gas plasma jets from a 100 kW DC plasma torch have been on the order of ~11,200 K [7], while the temperatures measured from a pulsed electrothermal plasma source range from 8,800 to 14,000 K [12,13]. Torres et al working on high-pressure hydrogen microwave plasma torches reported temperatures in the range of 9,500 to 10,700 K measured via optical emission spectroscopy and analyzed by three different methods [8].…”
Section: Introductionmentioning
confidence: 99%
“…The assumption of local thermodynamic equilibrium (LTE) is usually valid for thermal plasma torches, similarly for electrothermal plasma sources [7], [8], [12], [13]. Temperature measured in argon gas plasma jet from a 100-kW dc plasma torch was ∼11 200 K [7], while that from a pulsed electrothermal plasma source ranged from 8800 to 14 000 K [12], [13].…”
mentioning
confidence: 99%
“…Temperature measured in argon gas plasma jet from a 100-kW dc plasma torch was ∼11 200 K [7], while that from a pulsed electrothermal plasma source ranged from 8800 to 14 000 K [12], [13]. The work of Torres et al [8] on high-pressure hydrogen microwave plasma torch reported temperatures in the range of 9500-10 700 K measured via optical emission spectroscopy and analyzed by three different methods, which is consistent with typical plasma torches and electrothermal plasma sources.…”
mentioning
confidence: 99%